2008
DOI: 10.1002/pat.1294
|View full text |Cite
|
Sign up to set email alerts
|

Polydimethylsiloxane–cristobalite composite adhesive system for aerospace applications

Abstract: The effect of phase‐pure cristobalite (a high temperature crystalline polymorph of silica) on the adhesive characteristics of hydroxyl terminated polydimethylsiloxane (PDMS) was studied. The potential advantages of PDMS/cristobalite composite system as an adhesive for aerospace applications are also discussed. A PDMS/cristobalite composite adhesive system containing different filler contents (0–46 volume percentage, vol%) was prepared. The filler material, phase‐pure cristobalite, was synthesized by the pyroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…1 Its performance is superior to ordinary organic rubbers due to excellent chemical stability, high thermal resistance, outstanding insulating properties, low toxicity, 2 and very low glass transition temperature (T g ), as well as unique linear elasticity over a broad range of temperatures (À40 to 400 C) and strains. 3 However, the intermolecular forces among PDMS polymer chains are relatively weak since Si-O bond exhibits larger bond length than C-C bond. 4 Hence, PDMS polymer usually shows a low mechanical strength (0.1-0.4 MPa), which limits its mechanical component used in practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…1 Its performance is superior to ordinary organic rubbers due to excellent chemical stability, high thermal resistance, outstanding insulating properties, low toxicity, 2 and very low glass transition temperature (T g ), as well as unique linear elasticity over a broad range of temperatures (À40 to 400 C) and strains. 3 However, the intermolecular forces among PDMS polymer chains are relatively weak since Si-O bond exhibits larger bond length than C-C bond. 4 Hence, PDMS polymer usually shows a low mechanical strength (0.1-0.4 MPa), which limits its mechanical component used in practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…26,34 Additionally, a new characteristic peak at 620 cm À1 for sintered samples sintered at 1000 C was appeared, which was attributed to the characteristic peak of cristobalite. 35,36 It indicated that the quartz or amorphous silica had been transformed into the cristobalite at high temperature and the crystal structure of cristobalite could be further veried by XRD test.…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
“…한편, 폴리(디메틸 실록산) (PDMS)은 주사슬의 Si-O 결합 으로 인하여 매우 낮은 유리전이온도를 나타낼 뿐 아니라, 내 열성, 전단 안정성, 높은 유연성과 기체 투과성, 생체 적합성 등 우수한 특성을 나타낸다. [4][5][6] 따라서 PDMS가 포함된 세그 먼트 공중합체, 블록 공중합체 및 이들 공중합체와 단일 고 분자와의 블렌드 등 PDMS가 포함된 다성분계 고분자에 관 한 연구들이 활발히 이루어져 왔다. 7,8 이와 관련해서 저자들은 HS 성분으로 메틸렌 디페닐 디이 소시아네이트(MDI)와 1,4-부탄디올(BD)을 사용하고 SS 성분 으로 폴리(테트라메틸렌 에테르 글리콜)(PTMEG)과 PDMS 디올의 혼합 폴리올을 사용하면서, HS 함량과 PDMS 성분 비율이 다른 "PDMS 성분을 포함하는 PU(이하 PU-Si로 약 함)"를 용액중합법으로 합성하고, 이들의 열적 특성과 형상 기억 특성에 대해서 보고한 바 있다.…”
Section: 서 론unclassified